2011
DOI: 10.1136/postgradmedj-2011-130077
|View full text |Cite
|
Sign up to set email alerts
|

Primary IgA nephropathy in north India: is it different?

Abstract: Comparison of clinical and pathological features revealed that this disease presents as an advanced disease in much younger individuals in this study compared to other studies. Elucidation of the underlying factors may have immense therapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
0
16
1
Order By: Relevance
“…The mean age of their patients was 29.9 years with a male: female ratio of 4.4:1. They found that, most patients presented with renal failure and a significant percentage (23%) also had nephrotic range proteinuria (35). This finding is in contrast to our results because in our study, the mean of proteinuria and serum creatinine were 1795 ± 1369 mg/day and 1. hypercellularity, glomerular sclerosis, endocapillary hypercellularity and IFTA were associated with the renal outcome likelihood ratio (22).…”
Section: Discussioncontrasting
confidence: 56%
“…The mean age of their patients was 29.9 years with a male: female ratio of 4.4:1. They found that, most patients presented with renal failure and a significant percentage (23%) also had nephrotic range proteinuria (35). This finding is in contrast to our results because in our study, the mean of proteinuria and serum creatinine were 1795 ± 1369 mg/day and 1. hypercellularity, glomerular sclerosis, endocapillary hypercellularity and IFTA were associated with the renal outcome likelihood ratio (22).…”
Section: Discussioncontrasting
confidence: 56%
“…18,19,21 Endocapillary hypercellularity, crescents and segmental glomerulosclerosis were less common in our patients and proportion of tubulointerstitial lesions were similar compared to other studies from Asia. 18 The other Indian study by Mittal et al, 9 which has applied the Oxford criteria to kidney biopsies of IgAN patients has also reported a similar proportion of mesangial hypercellularity and segmental glomerulosclerosis (Table 4). However, compared to our patient cohort, their study had higher proportion of endocapillary proliferation (9.7% vs. 29.6%) and crescentic.…”
Section: Discussionmentioning
confidence: 78%
“…Alamartine et al 20 had 13.6%, Katafuchi et al 21 had 4% and the VALIGA cohort 22 had 9% patients with eGFR less than 30 mL/min. Other studies [7][8][9] have shown that a large proportion of Indian patients with IgA nephropathy have significant renal dysfunction at the time of biopsy; however, renal failure has not been well defined in these studies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There is relatively little information in literature on the population-based prevalence and clinicopathological features of IgAN in third world countries (3,(8)(9)(10). In particular, there are very few studies on the pathological characteristics of the disease according to the new Oxford-MEST classification from these parts of the world (8).…”
Section: Article Infomentioning
confidence: 99%